REVIEW OF THE IMPLEMENTATION OF CLEMENCY IN THE INDONESIAN CRIMINAL LAW SYSTEM: (Study of Constitutional Court Decision Number 32 / PUU-XIV/2016) - Setyaningrum, Putri Imaniar; Setiyono (Transpublika Publisher, 2021)
Clemency is a presidential privilege that entails changes, waivers, reductions, or the elimination of criminal executions granted by the President. The scope of clemency is defined in Law No. 5 of 2010, which amends Law No. 22 of 2002 concerning Clemency. The applicable ruling must have a permanent legal force (Inkracht). Clemency can be sought for individuals sentenced to death, life imprisonment, or a minimum sentence of 2 years in prison. This study focuses on the case of Suud Rusli, a death row inmate who unsuccessfully attempted to apply for clemency but was subsequently executed. The research aims to answer the following questions: